An Automated Rack Storage System for Railway Devices and Equipment Using QR Code and Cloud Database Technology - Sarong, Charm Angel R.; Ignacio, Aaliyah Mikaela A.; Guzarin, Chrizel R.; Valdueza, Rhen Jester; Delizo, Carlo Jay G.; Bunag, Sherlie D.; Aunario, Connie C.; Martin, Weellrr D.; Garcia, Julius G. (IC-ITECHS, 2024)
This research project aims to develop an automated storage rack system for railway devices and equipment using QR codes and cloud-based database technology. The automated rack system can precisely store railway devices and equipment using the cloud-based QRC/QR Code database. It explores the drawbacks of conventional storage management methods in the railway industry, like lack of order, inefficiency, and security issues. Using QR codes to track and monitor all tools, equipment, and components, the proposed system includes a cloud-based database providing real-time inventory visibility and data analysis capabilities. Additionally, the system features CCTV surveillance for added security level and mobile phone integration to ensure that only you, as the end user, get access. Based on the study's findings, automated storage rack systems promise significant improvements in efficiency, security, and operational effectiveness for railway maintenance.